Producing Knowledge in the Alps. Collaborative Research in Dairy Microbiology, 1960–Present - Elise Tancoigne (Revue de Géographie Alpine)
Mountain environments have long been the site and target of partner-oriented research policies which favour approaches based on the co-construction of research problems between development actors, professionals and scientists. Research on the French dairy sectors in the Alps and the Jura is an example of this situation. Taking the example of dairy microbiology and the emergence of the notion of “microbial terroir” in the Alps and the Jura, I propose in this article to answer the following question: how does one produce knowledge in an Alpine context? In the first part, I will present the different forms that this collaborative research has taken since the 1960s. In the second part, I will show how the notion of "microbial terroir” has emerged within these research systems and I will develop the idea that this participatory research remains a minority form of knowledge production in microbiology. I will base this work on an analysis of the reflexive literature published by these different research projects as well as on scientometric analyses and archival work carried out between 2016 and 2020 in the Northern Alps.